2018
DOI: 10.1371/journal.pone.0203985
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of mental distress before the Great East Japan Earthquake and the associated impact of an aged society: An ecological study

Abstract: Various studies have determined that the Great East Japan Earthquake (GEJE) caused mental distress among residents in affected areas. However, previous studies had not considered the prevalence of mental distress before the GEJE, and ignored the impact of an aged society on mental distress. Therefore, we aimed to describe the prevalence of mental distress before the GEJE in Miyagi Prefecture, Japan and elucidate the effect of an aged society on mental distress. We conducted an ecological study, using municipal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Across both samples we found relatively low levels of psychological distress, particularly considering the high levels of household destruction suffered by our samples and the already high levels of distress recorded in Miyagi Prefecture prior to the earthquake. 17 Studies in Fukushima over a period of 3 years after the Great East Japan Earthquake 18 and in Niigata in the 5 years consecutive to the 2004 earthquake in that prefecture 19 showed decreases in distress over time, and in our prospective multilevel models time was also the major contributor to variance in post-disaster distress. As elsewhere, effects for gender and previous psychiatric disorders persisted across waves: in previous studies women carried the heavier emotional burden post-disaster, 19 potentially as a result of their lesser access to positive social support.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Across both samples we found relatively low levels of psychological distress, particularly considering the high levels of household destruction suffered by our samples and the already high levels of distress recorded in Miyagi Prefecture prior to the earthquake. 17 Studies in Fukushima over a period of 3 years after the Great East Japan Earthquake 18 and in Niigata in the 5 years consecutive to the 2004 earthquake in that prefecture 19 showed decreases in distress over time, and in our prospective multilevel models time was also the major contributor to variance in post-disaster distress. As elsewhere, effects for gender and previous psychiatric disorders persisted across waves: in previous studies women carried the heavier emotional burden post-disaster, 19 potentially as a result of their lesser access to positive social support.…”
Section: Discussionmentioning
confidence: 65%
“…Ecological analyses conducted shortly before the earthquake suggest particular vulnerability among in-patients with mental illness. 17 Given that many of these institutions were severely disrupted during the Great East Japan Earthquake, special care must be taken to support those with enduring clinical vulnerabilities in newly dispersed communities. Where records survive, clinicians may seek out those with pre-existing diagnoses and offer targeted support if required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such uncertain social contexts, people experience various anxieties in their lives [36]. With regard to the relationship between health and uncertainty in society, previous researches have reported that uncertain social contexts, such as social inequality, economic recession, and ageing population are harmful to health [3739]. Furthermore, previous studies have shown that various anxieties in life, such as job insecurity, adversely affect the health of individuals experiencing them [40, 41].…”
Section: Introductionmentioning
confidence: 99%